The Racial Discrimination in the 12 Years A Slave Novel by Solomonon Nrthup Towards the Supporting Character Patsey (Marxist Feminism Persective) - Sumaga, Safira Deviani; Katili, Adriansyah; Podungge, Rusni (Jurnal Bahasa, Sastra, dan Budaya, 2024)
This research examines racial discrimination towards Patsey in Solomon Northup's 12 Years A Slave novel. The study aims to categorize racial discrimination types using Gordon Allport's (1954) theory—verbal abuse, avoidance, segregation, physical attack, and extermination—analyzing through Marxist feminism. Utilizing a qualitative sociological method, the research identifies three discrimination types: verbal antagonism, avoidance, and physical attack. Segregation and extermination were not evident. In the verbal antagonism stage, Mr. Epps verbally degraded Patsey's race and gender, labeling her a black wench. The avoidance stage portrays Mrs. Epps, an upper-class woman, expressing resentment by withholding food and soap, illustrating power dynamics. The physical attack stage illustrates Patsey being flogged for not meeting cotton-picking quotas, showcasing the compounded oppression faced by women slaves in race, gender, and class. Patsey's abuse by Mr. and Mrs. Epps for their master's mistakes highlights how upper-class individuals perpetuate oppression. Patsey's naked punishment underscores gender-specific oppression. In conclusion, Patsey's narrative in 12 Years A Slave novel exemplifies race and gender intersectionality, revealing capitalism and patriarchy collaboration in marginalizing lower-class black women.